LEXICOGRAPHIC PRINCIPLES IN THE INTERPRETATION OF TOPONYMS IN ENGLISH (IN THE EXAMPLE OF BRITISH AND AMERICAN PLACE NAME DICTIONARIES) (Scientific journal of the Fergana State University, 2023)
In this article, English toponyms and their interpretation in toponymic dictionaries are discussed separately.Placement of toponyms in dictionaries, their specific lexicographic features, as well as lexicography and scientists who conducted scientific research in this field are discussed in detail. Their work is reflected in the article and the reaction is expressed. At the same time, special attention is paid to toponymic dictionaries, their authors, approaches and methods and principles presented in each dictionary section.The practical importance of the article is that two authoritative toponymic dictionaries are compared in its main part.The same toponymic units listed in both dictionaries are selected, and the state of interpretation given in the dictionary, that is, the originality, is shown. The similarities and differences are compared. The interpretations are analyzed.